'Not here for geopolitical interests or games': the EU's 2019 strategy and the regional and inter-regional competition for Central Asia. Issue 4 (2nd October 2022) - Fawn, Rick
ABSTRACT: The European Union's (EU) 2019 New Strategy for Central Asia and joint meetings with Central Asia's five foreign ministers established standards and expectations for mutual relations. Throughout those initiatives and proclamations, the EU stresses its un-geopolitical essence and behaviour, including the statement that affords the article's title. The article identifies five issue areas that demonstrate that, despite declarations otherwise, the EU reasons and acts geopolitically in this contested region: (1) the promotion of Central Asian regionalism; (2) the inclusion of Central Asia in formations beneficial to the EU; (3) selectively in economic and functionalist cooperation; (4) democracy, human rights and civil society promotion; and (5) international education cooperation. The EU identifies its comparative advantage through cost–benefit analyses and seeks to enhance its attractiveness by offering its allies to Central Asia, while excluding other, present actors. That the EU is often outmanoeuvred does not diminish this subtle yet discernible geopolitical conduct.